2009
DOI: 10.4319/lo.2009.54.6.1863
|View full text |Cite
|
Sign up to set email alerts
|

Physical and biogeochemical limits to internal nutrient loading of meromictic Lake Kivu

Abstract: Lake Kivu is one of the large African Rift lakes situated between the Democratic Republic of the Congo and Rwanda. In its permanently stratified hypolimnion, unusually high methane concentrations have increased further in recent decades. Because methanogenesis is, in part, dependent on supply of organic material from the photic zone, it is necessary to quantify upward nutrient fluxes from the saline, nutrient-rich deep waters. These upward fluxes are mainly driven by advection caused by subaquatic springs. Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
67
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 28 publications
11
67
1
Order By: Relevance
“…The depth profiles of ammonium concentration were comparable for both Ursu and Fara Fund lakes, and similar to the ones described in other stratified lakes (Auguet et al, 2012;La Cono et al, 2013;Yau et al, 2013). The vertical profiles of nutrients (sulfate, sulfide, nitrite, nitrate and phosphate) were found to be a result of sedimentation, biogeochemical cycling or conservative mixing (Pasche et al, 2009), and were also comparable with those found in other studied lakes (Lepère et al, 2010;La Cono et al, 2013;Marteinsson et al, 2013).…”
Section: Water Chemistrysupporting
confidence: 68%
“…The depth profiles of ammonium concentration were comparable for both Ursu and Fara Fund lakes, and similar to the ones described in other stratified lakes (Auguet et al, 2012;La Cono et al, 2013;Yau et al, 2013). The vertical profiles of nutrients (sulfate, sulfide, nitrite, nitrate and phosphate) were found to be a result of sedimentation, biogeochemical cycling or conservative mixing (Pasche et al, 2009), and were also comparable with those found in other studied lakes (Lepère et al, 2010;La Cono et al, 2013;Marteinsson et al, 2013).…”
Section: Water Chemistrysupporting
confidence: 68%
“…In the intermediate 60-90 m zone, the upward (diffusing and advective) fl uxes of HS -are greater than the downward fl uxes of SO 4 2− (Pasche et al 2009 ) . The inverse pro fi les of HS -and SO 4 2− observed in this zone are mainly explained by O 2 -driven sul fi de oxidation.…”
Section: Lake Kivu and Potential Microbial Processes In Upper And Intmentioning
confidence: 99%
“…In Lake Kivu, the inverse pro fi les of CH 4 and SO 4 2− in the intermediate zone from 60 to 90 m (Pasche et al 2011 ) suggest the relevance of this process. Nevertheless, the sulfate fl ux budget indicates that only 3% of the CH 4 would be oxidized with SO 4 2− (Pasche et al 2009(Pasche et al , 2011 . This estimate is a maximum because sulfate reducers can also use organic matter as an electron donor, pursuing anaerobically the heterotrophic decomposition of settling phytoplankton.…”
Section: Lake Kivu and Potential Microbial Processes In Upper And Intmentioning
confidence: 99%
See 1 more Smart Citation
“…In anoxic systems, sulphate reduction in the sediments and the release of reduced substances like NH 4 + further contribute to an increase of alkalinity with depth (Pasche et al, 2009). Precise profiling of alkalinity (Stumm and Morgan, 1996) in stratified waters is therefore essential to quantify the dynamics of the carbon cycle, to constrain the pathways of organic carbon mineralisation, and to understand the burial of carbonates in the sedimentary record (Schrag et al, 2013).…”
mentioning
confidence: 99%